Investigation of the Causes of Malfunctions of Special Electrical Equipment of Pumping Stations - et. al., AyubjonVokhidov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The task of this work was to consider the main technical parameters of pumping stations that affect the operating modes and the overall reliability of a special power supply system. Also, the technological processes of the irrigation pumping station were investigated and the analysis of mechanical and parametric characteristics, the causes of the asynchronous operation of mechanisms and the failure of the pumping units themselves was carried out. As a result of the work, a method for calculating the voltage drop was proposed, a new independent algorithm for calculating the static stability and the stability margin for the active power of special electrical equipment was developed.